Digital matrix : new rules for business transformation through technology - Venkatraman, Venkat (Gurgaon Penguin Random House, 2017)
Ambitious digital-driven startups are now creating and cornering new markets in every sector. And yet, most legacy businesses continue to operate by old playbooks. Most are not keeping pace with the changes in their industry, let alone leading the way-what is yours doing? The Digital Matrix will help you understand the three types of players that are shaping the new business landscape; the three phases of transformation that every firm will encounter on its journey to business reinvention; and the three winning moves that will ensure your company's success along the way.With The Digital Matrix, you will: Learn to navigate the world of digital ecosystems. Discover ways of competing and collaborating with other companies to create and capture value. Realize how powerful machines can amplify your company's human talent. Learn to assemble the team to experiment with new ideas, re-examine your core beliefs and reinvent your business rulebook for the digital future. Your company's future depends on its ability to harness digital technology.Don't wait!
Keywords: Success in business